Standardization of microparticle enumeration across different flow cytometry platforms: results of a multicenter collaborative workshop - Cointe, S.; Judicone, C.; Robert, S.; Mooberry, M. J.; Poncelet, P.; Wauben, M.; Nieuwland, R.; Key, N. S.; Dignat‐George, F.; Lacroix, R. (Journal of thrombosis and haemostasis, 2017)
Essentials The clinical enumeration of microparticles (MPs) is hampered by a lack of standardization. A new strategy to standardize MP counts by flow cytometry was evaluated in a multicenter study. No difference was found between instruments using forward or side scatter as the trigger parameter. This study demonstrated that beads can be used as a standardization tool for MPs. Click to hear the ISTH Academy's webinar on microvesicles Summary Background Microparticles (MPs) are extracellular vesicles resulting from the budding of cellular membranes that have a high potential as emergent biomarkers; however, their clinical relevance is hampered by methodological enumeration concerns and a lack of standardization. Flow cytometry (FCM) remains the most commonly used technique with the best capability to determine the cellular origin of single MPs. However, instruments behave variably depending on which scatter parameter (forward (FSC) or side scatter (SSC)) provides the best resolution to discriminate submicron particles. To overcome this problem, a new approach, based on two sets of selected beads adapted to FSC or SSC‐optimized instruments, was recently proposed to reproducibly enumerate platelet‐derived MP counts among instruments with different optical systems. Objective The objective was to evaluate this strategy in an international workshop that included 44 laboratories accounting for 52 cytometers of 14 types. Methods/Results Using resolution capability and background noise level as criteria to qualify the instruments, the standardization strategy proved to be compatible with 85% (44/52) of instruments. All instruments correctly ranked the platelet MP (PMP) levels of two platelet‐free plasma samples. The inter‐laboratory variability of PMP counts was 37% and 28% for each sample. No difference was found between instruments using forward or side‐scattered light as the relative sizing parameter. Conclusions Despite remaining limitations, this study is the first to demonstrate a real potential of bead‐based strategies for standardization of MP enumeration across different FCM platforms. Additional standardization efforts are still mandatory to evaluate MPs’ clinical relevance at a multicenter level.